"My whole room went into chaos because of that thing in the corner": Unintended consequences of a central fetal monitoring system. (November 2021) - Small, Kirsten; Sidebotham, Mary; Gamble, Jenny; Fenwick, Jennifer
Abstract: Objective: Technologies for fetal heart rate monitoring have been widely introduced despite evidence of no improvement in perinatal outcomes. A significant body of research has raised concerns that healthcare information technologies can have unintended consequences. We sought to describe an unintended consequence of central fetal monitoring technology. Design: The research was conducted as an Institutional Ethnography. Data generated from interviews, focus groups, and observations were analysed to generate an account of midwives' experiences with the central fetal monitoring system. Setting: The birthing unit of one Australian maternity service with a central fetal monitoring system. Informants: 34 midwives and midwifery students who worked with the central fetal monitoring system. Findings: Midwives described a disruptive social event they named being K2ed . Clinicians responded to perceived cardiotocograph abnormalities by entering the birth room despite the midwife not having requested assistance. Being K2ed disrupted midwives' clinical work and generated anxiety. Clinical communication was undermined, and midwives altered their clinical practice. Midwives performed additional documentation work to attempt to avoid being K2ed . Key conclusions: This is the first report of an unintended consequence relating to central fetal monitoring, demonstrating how central fetal monitoring technology potentially undermines safety by impacting on clinical and relational processes and outcomes in maternity care. Implications for practice: Current evidence does not support implementation or ongoing use of central fetal monitoring systems. Further research is needed to inform scaling down central fetal monitoring systems in a safe and supported way.